Espacios 2020
DOI: 10.48082/espacios-a20v41n45p01
|View full text |Cite
|
Sign up to set email alerts
|

Rentabilidad de las empresas agrarias colombianas y sus determinantes sectoriales y de localización

Abstract: En este trabajo se usó información de los registros mercantiles para caracterizar la evolución del sector agrario colombiano sobre los efectos sectoriales y de localización ejercidos en la rentabilidad de sus empresas en el periodo 2014 a 2017. Se halló una mayor rentabilidad en función de la ubicación de las empresas que entre los diferentes tipos de actividades agrarias, lo que amerita políticas estructurales y estrategias comerciales diferenciales para acotar la brecha tecnológica y socioeconómica en los te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Studies based on the Location theory highlight the positive effects on profitability derived from firms' location (Arias et al, 2020). Empirically, differences in profitability that firms present beyond firm-specific and industry-specific factors, are attributed to the location effect by authors such as Castro et al (2019), Makino et al (2004) and Pereira et al (2011).…”
Section: Location Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies based on the Location theory highlight the positive effects on profitability derived from firms' location (Arias et al, 2020). Empirically, differences in profitability that firms present beyond firm-specific and industry-specific factors, are attributed to the location effect by authors such as Castro et al (2019), Makino et al (2004) and Pereira et al (2011).…”
Section: Location Factorsmentioning
confidence: 99%
“…Both provide key information to design firms’ future strategies (Zainudin et al., 2018). We approach the analysis from these two perspectives including: (i) firm‐specific factors, linked to firms’ market power (Ponikvar & Tajnikar, 2012); some studies found them to be the most important factor to explain business results (Blažková & Dvoulety, 2018; González et al., 2000; McGahan & Porter, 1997, 2002; Rumelt, 1991); (ii) industry‐specific factors, which analyze the extent to which the characteristics of the industry to which the firm belongs are linked to their results (González et al., 2000; McGahan & Porter, 1997); (iii) location factors, which base the explanation on the effects of agglomeration and spatial location (Arias et al., 2020; Castro et al., 2019; Krugman, 1991). There is one principal research question: Are there significant differences in cooperatives’ profitability depending on firm‐specific, industry‐specific and/or location factors?…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations